PERBANDINGAN IMPLEMENTASI UNDANG-UNDANG NO. 03 TAHUN 1997 DENGAN UU NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN ANAK - Chaerudin, Ilham; Nur muhammad, Aditya; Maulana, Oja; Maruf faisal, Anang (Gayaku Publisher, 2024)
Indonesia is a state of law, of course, as stated in Article 1 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Indonesia is a State of Law, meaning that human rights (HAM) are the main element that must be protected, upheld and fulfilled by the state, so in this case both the government and state institutions authorized to discipline and prosecute every citizen are legally obliged to guarantee the rights of every Indonesian citizen including children. Law No. 11/2012 on the Juvenile Criminal Justice System, Law No. 39 on Human Rights, and Law No. 23/2002 on Child Protection are legally required to protect children. In Indonesia, the juvenile criminal justice system is regulated in the first legislation Law No. 3 of 1997 and then replaced with a new article and which is currently in effect or has become positive law, namely Law No. 11 of 2012. As for this discussion, the author will discuss the comparison of the IMPLEMENTATION of Law No. 03 of 1997 with Law No. 11 of 2012 concerning the Juvenile Justice System. Where in this study we will compare what are the similarities and differences that exist in the Old Criminal Justice System with the New. In this case the author uses a normative juridical research method in which the research is carried out by analyzing the law through document studies, namely using sources of legal material in the form of laws and regulations, court decisions / decrees, contracts / agreements / contracts, legal theories, and opinions of scholars. Based on the research that has been researched, it can be concluded that the most striking comparison of the legislation lies in the step of resolving the case, where in the new law there is a restorative justice method or better known as the diversion method, which is the resolution of disputes / problems outside the court by bringing together the two parties concerned and offering peace.